Prebiotics in Management of Neonatal Jaundice: Open Label Randomised Control Trial - Trupti Amol Joshi; Amol Kalyanrao Joshi; Laxmikant Sheshrao Deshmukh (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Approximately 5-35% of neonates develop jaundice requiring treatment during the 1st week of life. Prebiotics, a mixture of Galacto-oligosaccharides (GOS) and Fructo-oligosaccharides (FOS), has been postulated to reduce serum bilirubin levels on principle of interruption of entero-hepatic circulation. Objective: To evaluate the effect of oral supplementation with prebiotics (Fructo-oligosaccharides) in the management of neonatal jaundice. Subjects and Methods: Design & Setting: Open Label, Randomized Control Trial at Level II NICU in public hospital over one year. Participants: Term exclusively breast-fed neonates with Jaundice requiring phototherapy. Intervention: Randomisation of Sixty eligible neonates into Control and Prebiotic groups (n= 30 each). Both groups received phototherapy, and Prebiotic group received additional oral prebiotics.  Outcome: Primary outcome measure was a reduction in total serum bilirubin levels (TSB) and duration of phototherapy. The secondary outcome measure was the change in the frequency of stools.Results: Baseline Features were similar in both groups. Overall serum bilirubin levels decreased significantly from enrolment till the omission of phototherapy (17.24 + 1.16 vs. 12.74 + 0.48; P: 0.00). ANOVA depicted no statistical difference between the groups in 12 hourly reductions of TSB (F [3, 232] = 0.14, P: 0.94). Mean duration of phototherapy (in hours) required in prebiotic and control group was similar (50.40 + 9.66 vs. 47.60 + 8.62; P = 0.24). Secondary outcome measures were also similar in both groups.Conclusion: Prebiotics, containing only fructo-oligosaccharides, administered for upto three days, do not have any additional effect on reduction of serum bilirubin levels in neonates with jaundice receiving conventional treatment.